Revisionism of Vargas’ revisionism: Free will, Disagreements, Common Sense from Neo-Pyrrhonism - Reinoso, Guadalupe (Analysis. Journal of Philosophical Research, 2021)
From an overview of philosophy, it can be said all issues are controversial. An example of this kind of never-ending controversy is the free will debate. The originality of Revisionism proposed by Vargas (2007, 2013) is to establish a position within the debate after having reviewed the terms in which it is discussed. His Revisionism focuses on reviewing how the different philosophical positions of the debate are linked to the intuitions or preconception of common sense. Vargas argues that common sense –as a preconception- has incompatibilistic elements that ought to be accepted when making a diagnosis. However, at a prescriptive level, the theory that ought to be adopted in philosophy is compatibilism. Thereby, Vargas proposes a hybrid Revisionism.By reading Wittgenstein from a neo-Pyrrhonic orientation, I propose to reconsider the role of disagreement in the philosophical debate and the approach to common sense in order to argue that it is a plural set of practices rather than a preconception. These practices determine different contexts for the use of concepts, in which both deterministic and indeterministic positions can make sense. This pluralistic view of common sense also modifies the place of philosophy and the kind of disagreement faced in the debate.